Flubendazole carbonyl reduction in drug-susceptible and drug-resistant strains of the parasitic nematode Haemonchus contortus: changes during the life cycle and possible inhibition - Rychlá, Nikola; Navrátilová, Martina; Kohoutová, Eliška; Raisová Stuchlíková, Lucie; Štěrbová, Karolína; Krátký, Josef; Matoušková, Petra; Szotáková, Barbora; Skálová, Lenka (Veterinary research, 2024)
Carbonyl-reducing enzymes (CREs) catalyse the reduction of carbonyl groups in many eobiotic and xenobiotic compounds in all organisms, including helminths. Previous studies have shown the important roles of CREs in the deactivation of several anthelmintic drugs (e.g., flubendazole and mebendazole) in adults infected with the parasitic nematode Haemonchus contortus, in which the activity of a CRE is increased in drug-resistant strains. The aim of the present study was to compare the abilities of nematodes of both a drug-susceptible strain (ISE) and a drug-resistant strain (IRE) to reduce the carbonyl group of flubendazole (FLU) in different developmental stages (eggs, L1/2 larvae, L3 larvae, and adults). In addition, the effects of selected CRE inhibitors (e.g., glycyrrhetinic acid, naringenin, silybin, luteolin, glyceraldehyde, and menadione) on the reduction of FLU were evaluated in vitro and ex vivo in H. contortus adults. The results showed that FLU was reduced by H. contortus in all developmental stages, with adult IRE females being the most metabolically active. Larvae (L1/2 and L3) and adult females of the IRE strain reduced FLU more effectively than those of the ISE strain. Data from the in vitro inhibition study (performed with cytosolic-like fractions of H. contortus adult homogenate) revealed that glycyrrhetinic acid, naringenin, mebendazole and menadione are effective inhibitors of FLU reduction. Ex vivo study data showed that menadione inhibited FLU reduction and also decreased the viability of H. contortus adults to a similar extent. Naringenin and mebendazole were not toxic at the concentrations tested, but they did not inhibit the reduction of FLU in adult worms ex vivo.
Keywords: Strongyloides; helminths; Mebendazole; vitamin K 3; kyselina glycyrhetinová; Anthelmintics; Vitamin K 3; Glycyrrhetinic Acid; larva; Animals; ženské pohlaví; inhibitors; anthelmintika; zvířata; drug biotransformation; Larva; Female; Haemonchus; mebendazol